Analisis Pengaruh Motivasi Kerja Terhadap Kinerja Pegawai - Rina Ari Rohmah (Fakultas Ekonomi Universitas Pasir Pengaraian, 2019)
The purpose of this study was to determine the Work Motivation and Work Environment on Employee Performance, both partially and simultaneously. The population in this study was the Civil Service Police Unit Rokan Hulu Regency, with a total sample of 84 people. The independent variables in this study are Work Motivation (X1), and Work Environment (X2), and the dependent variable is Performance (Y). Methods of data collection using questionnaires, observations, and interviews. The results showed that (1) Partial Tests between Work Motivation variables have a significant and positive influence on Employee Performance. This is evidenced by the t-test where Work Motivation count 7.063> table 1.663. (2) Partial testing between the Work Environment has a significant and positive effect on performance, this is evidenced by the t-test where the Work Environment T-count 3.407> t table 1.663 and (3) the relationship simultaneously Work Motivation, and the Work Environment has a positive and significant effect which is proven with the F test the value of F-count 71.167> F table 3.11. So the hypothesis which states that there is a significant influence of Work Motivation and Work Environment on employee performance is accepted.